COMPARATIVE PHYSICOCHEMICAL, PHYTOCHEMICAL AND HIGH PERFORMANCE THIN LAYER CHROMATOGRAPHY EVALUATION OF HEART WOOD AND SMALL BRANCHES OF AQUILARIA AGALLOCHA ROXB. (International Journal of Ayurveda and Pharma Research, 2016)
Aquilaria agallocha Roxb. commonly called as Agaru is a medicinal plant. Heartwood of this tree is widely used in Ayurveda for various diseases. Removal of heart wood from trunk of this tree may make this plant weak and susceptible to damage due to which availability of this plant may be difficult in near future. Present study outlines the concept of plant part substitution. Heart wood and small branches of A. agallocha are compared on the basis of physicochemical analysis, phytochemical analysis, total phenolic contents, total flavonoid contents and high performance thin layer chromatography (HPTLC) to evaluate the possibilities of using small branches instead of heart wood. Physicochemical parameters of heartwood and small branches and phytochemical analysis of n-hexane, ethyl acetate and ethanol extract of both heart wood and small branches were carried out using standard methods. Total phenolics and total flavonoids were estimated spectrophotometrically using Folin-ciocalteu assayand aluminum chloride assaymethods, respectively. CAMAG HPTLC system equipped with semi-automatic applicator was used for HPTLC of n-hexane, ethyl acetate and ethanol extracts of stem bark and small braches using suitable mobile phases. Results of phytochemical analysis and HPTLC of n-hexane, ethyl acetate and ethanol extracts showed many similarities whichsuggest that small branches may have nearly similar active potency like heart wood and may be used as a substitute of heart wood after comparison and confirmation of same for pharmacological activities.